Formation of base-populations of meat-type chickens using diallel crosses of commercial strains. II. Evaluation of the body weight - Schmidt, Gilberto S.; Packer, Irineu Umberto; Duarte, Francisco Alberto de Moura; Costa, Cláudio Napolis (Pesquisa Agropecuaria Brasileira, 1991)
This study was carried out at the Centro Nacional de Pesquisa de Suínos e Aves (National Swine and Poultry Research Center/EMBRAPA) with the objective of testing four commercial strains of meat-type chickens using diallel crosses. There were four male lines and four female lines, identified by L (L1, L2, L3 and L4) and P (P1, P2, P3 and P4), respectively. The analysis of diallel crosses among strains, within male and female lines was based on body weight at 42 days. There were significant differences among crosses on body weight and reciprocal effects, general and specific combining ability. The lines that showed best results for body weight at 42 days were P2 and L2.
Keywords: poultry breeding; body weight; meat-type chickens